Lord Edgware dies : a Hercule Poirot mystery - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Hercule Poirot mysteries, 2025)
"In this official authorized edition from the Queen of Mystery, detective Hercule Poirot must solve a most confounding conundrum when Lord Edgware has a most unnatural death. When Lord Edgware is found murdered the police are baffled. His estranged actress wife was seen visiting him just before his death and Hercule Poirot himself heard her brag of her plan to "get rid" of him. But how could she have stabbed Lord Edgware in his library at exactly the same time she was seen dining with friends? It's a case that almost proves to be too much for the great Poirot." --